EVALUASI KINERJA ANGKUTAN UMUM (MIKROLET) RUTE TONDANO-TOMOHON - Brando I. Mukuan; Yessy C. S. Pandeirot; Toar U. Y. Pangkey (Sustainable Construction (SUSCON), 2024)
Transportation is important for the increasing need for transportation services for the mobility of people and goods. Transportation is a type of public transportation used in daily activities in various places. This research aims to 1) find out how much tariffs should be applied, 2) find out whether the tariffs currently in effect are appropriate for transportation users, 3) find out whether the tariffs currently in effect can be profitable for entrepreneurs or not. This research was conducted on the Tondano – Tomohon bus route for 6 days. Data analysis uses the FSTPT method and the DLLAJ method. The results of this research show that the appropriate tariff for the FSTPT method is Rp. 9,000, and for the DLLAJ method it is Rp. 9,200. From the financial analysis, with a discount factor of 10%, 7% and 5%, the rates obtained from the two methods above can both produce profits for operation for the next 10 years. The results of the analysis using the FSTPT and DLLAJ methods show that the tariff set by operators or drivers for public transportation, especially the Tondano - Tomohon microbus route, is suitable for transportation users, namely IDR 10,000. The results of the financial analysis for the current tariff of IDR 10,000/pnp, can produce profits for the next ten years.